In-silico Screening of Compounds Contained in Wera (Malvaviscus Arboreus Cav.) Leaves as Anti-alopecia with Androgen Receptors - R. Mustarichie (Journal of Global Pharma Technology, 2019)
Objective: Baldness (Alopecia) is a serious problem at this time because it is caused by stress, genetic factors, pregnancy, inadequate hair care, and less balanced nutrition. Previous studies have shown that ethanol extracts of Wera leaves (Malvaviscus arboreus) have anti-baldness properties. Research study was undertaken to investigate the potential of chemical compounds contained in the leaves of Wera as hair growers using androgen receptors with comparative drugs Minoxidil. Methods: This type of research is in silico where the results obtained are free energy values and hydrogen bonds that connect ligands with receptors. Results: From the 7 compounds contained in the Wera leaf, the results showed that trifolin compounds gave the lowest energy -7.08 kcal/mol and amino acids that were bound were Thr (877), Asn (705), and Phe (764) where more than the comparative drug Minoxidil namely Leu (873) and Asn (705) with free energy is -5.81 kcal/mol. In predicting pharmacokinetic properties and toxicity tests, compounds that are predicted as candidates for hair growth drugs do not meet pharmacokinetic parameters and are non-mutagenic and not carcinogenic so they cannot be administered orally. Conclusion: It is found that molecules with compounds 2- [2- (5-methyl-2-propane-2-ylphenoxy) ethoxy] naphthalene-1-carboxylate provides the lowest energy, which is -9.47 kcal/mol so that it has the potential to be a candidate for a new drug in the treatment of hair growth, namely alopecia either oral or topical usedKeywords: Wera leaves, In-Silico, Hair growers, Androgen receptors, Malvaviscus arboreus.